Optimization management of investment for coal mines based on neural network model - Churikanova, Olena; Lysenko, Maryna (Management and Entrepreneurship: Trends of Development, 2019)
The main objective of the paper is to develop a system of economic and mathematical models for managing the investment activity of the coal mining enterprise, including improving the principles and methods for analyzing the profitability of investment projects and the optimal allocation of investments. Therefore, the article addressing the following issues: to determine the objectives of investment activity in coal mining enterprises; to systematize and identify statistically significant factors influencing investment activity in coal mining enterprises - affecting investment in coal mines; to form an economic-mathematical model for determining the amount of money that a coal-mining enterprise can allocate to investing; to form an economic-mathematical model for determining the enterprises profit as a result of the investment project implementation; to demonstrate expediency and perspective of the complex of developed model’s implementation, to check their practical efficiency; With the help of neural networks, a model was built based on 12 kinds of investment (9 kinds of investments into equipment, capital investment, portfolio investment, intangible assets investments) which are the most typical for a coal-mining enterprise. The method of optimization of investment allocation on a coal mine was developed, which, in contrast to the existing ones, determines the optimal investment volume, which helps to maximize profits for 12 investment models. As a result the method of optimization of investment allocation on a coal mine was developed, which, in contrast to the existing ones, determines the optimal investment volume, which helps to maximize profits for 12 investment models. JEL Classification: C45, E22, L72. https://doi.org/10.26661/2522-1566/2019-3/09-03